"Sing to the Lord no threadbare song": theological angularity in the face of Advent sentimentality - Witvliet, John D. (Interpretation, 2008)
To ward off Advent sentimentality, preachers and church musicians need to find theologically robust approaches to proclaiming the simultaneously sobering and glorious eschatological themes of Advent. Classical Christian doctrines, brought to life by theologically astute contemporary hymnwriters, offer many promising angles of vision for worshipers, preachers, teachers, and theologians.